Diagnostic Accuracy Of Magnetic Resonance Imaging (MRI) In The Diagnosis Of Meniscal Tears, Keeping Arthroscopy As The Gold Standard - Bashir, Shahid; Akhtar, Rahman Rasool; Mirza, Asad Noor; Sajid, Muhammad; Javaid, Muhammad Zubair; Arif, Adnan (Journal of Rawalpindi Medical College, 2025)
Objective: To evaluate the accuracy of magnetic resonance imaging (MRI) in diagnosing meniscal tears. Methods: A descriptive, cross-sectional validation study was carried out for 1 year on 71 patients who fulfilled the selection criteria after written informed consent. All patients had MRIS of the affected knee, and then arthroscopy was performed. Results: On MRI, the diagnosis of meniscal tear was made in 29 (40.8%) patients. Arthroscopy confirmed meniscal injury in 30 (42.3%) cases. The sensitivity, specificity, PPV, NPV and accuracy of MRI for diagnosing meniscal tears were 86.5%, 92.7%, 89.7%, 90.4% and 90.1%, respectively, keeping arthroscopic findings as the gold standard. Conclusion: In patients with meniscal tears, MRI showed a high sensitivity and specificity and an accuracy of keeping arthroscopy as the gold standard and thus can be used as a non-invasive screening tool for establishing the diagnosis in patients who have a suspicion of meniscal tear.